Proteomic analysis of zebrafish (Danio rerio) embryos exposed to cyclosporine A. - Ponnudurai, R; Basak, T; Ahmad, S; Bhardwaj, G; Chauhan, R; Singh, R; Lalwani, M; Sivasubbu, S; Sengupta, S (Elsevier, 2012)
Cyclosporine A, a potent immunosuppressive agent extensively used to prevent allograft rejections, is under scrutiny due to severe toxic effects. CsA therapy is often continued during pregnancy in conditions such as organ transplantations and autoimmune diseases. Herein, we investigated the effects of CsA on early morphogenesis of zebrafish and identified a spectrum of proteins whose expression was altered in the drug treated embryos. Time-lapse fluorescence imaging of germ-line double transgenic zebrafish embryos treated with CsA revealed severe blood regurgitation in heart chambers, absence of blood circulation in vessels, pericardial and yolk sac edema. We also observed lack of mature blood vessels and down-regulation of endothelial markers in CsA treated embryos. Proteomic analysis using 2D-DIGE followed by mass-spectrometry led to the identification of 37 proteins whose expression was significantly modulated in presence of the drug. These proteins were mostly associated with cytoskeletal/structural assembly, lipid-binding, stress response and metabolism. Furthermore, mRNA expression analysis of eight proteins and Western blotting of actin revealed consistency between the changes observed in protein expression and its corresponding mRNA levels. Our findings demonstrate that CsA administration during early morphogenesis in zebrafish modulates the expression of some proteins which are known to be involved in important physiological processes.